Cellulose-based broadband lightweight multilayer wave-absorbing material and preparation method thereof
Patent Information
- Application Number
- CN202611271826.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-08-20
- Publication Date
- 2026-10-27
AI Technical Summary
传统吸波材料如铁氧体、金属微粉等磁性材料密度大、频带窄,难以满足宽频使用需求
碳系材料具有低密度、高介电损耗的优势,但缺乏磁损耗,阻抗匹配性差,损耗能力弱。因此将碳系材料与磁性材料复合是获得性能协同的有效途径。
Smart Images

Figure CN122992335A_ABST
Abstract
Description
Technical Field
[0001] This invention relates to the field of microwave absorbing materials technology, and in particular to a cellulose-based broadband lightweight multilayer microwave absorbing material and its preparation method. Background Technology
[0002] With the rapid development of electronic communication technology, electromagnetic pollution is becoming increasingly serious, placing higher demands on electromagnetic protection and the compatibility of electronic equipment. An ideal absorbing material should meet the characteristics of being "thin, light, strong, and wide," meaning thin, lightweight, high-loss, and wide-bandwidth. Traditional absorbing materials, such as ferrites and metal powders, have high density and narrow bandwidth, making them unsuitable for wideband applications. Summary of the Invention
[0003] This invention provides a cellulose-based broadband lightweight multilayer microwave absorbing material and its preparation method, which can provide a lightweight broadband multilayer microwave absorbing material.
[0004] In a first aspect, embodiments of the present invention provide a method for preparing a cellulose-based broadband lightweight multilayer microwave absorbing material, comprising: Multiple groups of slurries are prepared, the slurries comprising carbon-based materials, magnetic materials, and a cellulose matrix; wherein, the amounts of carbon-based materials and magnetic materials added in different groups of slurries are different, so that the dielectric constants of the different groups of slurries are different after curing; Multiple sets of slurries are cured so that each set of slurries forms a composite layer after curing, resulting in a multilayer microwave absorbing material. In the multilayer composite layer of the multilayer microwave absorbing material, the dielectric constant gradient decreases from the bottom layer to the top layer; the top layer is the layer that receives electromagnetic waves.
[0005] Optionally, the carbon-based material is one of graphene, carbon nanotubes, and carbon black; the magnetic material is an iron-silicon-aluminum magnetic material modified with nanocellulose; and the cellulose matrix is nanocellulose.
[0006] Optionally, the slurry further includes a crosslinking agent, which is a mixture of citric acid and phytic acid.
[0007] Optionally, the mass ratio of citric acid to phytic acid is 1:3 to 3:1, and the total amount of crosslinking agent added is 5% to 30% of the mass of nanocellulose.
[0008] Optionally, the mass ratio of the carbon-based material to the magnetic material in the slurry is 1:10 to 10:1; the total filling amount of the carbon-based material and the magnetic material in the slurry accounts for 5% to 40% of the weight of the cellulose matrix layer.
[0009] Alternatively, the nanocellulose-modified iron-silicon-aluminum magnetic material is prepared by the following method: The mixture of nanocellulose solution and iron-silicon-aluminum powder at a mass ratio of 1:5 to 5:1 was ultrasonically dispersed and then freeze-dried to obtain the product; wherein the particle size of the iron-silicon-aluminum powder was 1 to 50 μm.
[0010] Optionally, the curing method of the slurry includes sequential directional freeze drying and thermal crosslinking curing.
[0011] Optionally, the process parameters for directional freeze drying are as follows: the directional freezing temperature is -80℃ to -20℃, the freezing rate is 0.5 to 5℃ / min, the vacuum degree of vacuum freeze drying is less than 20Pa, and the drying time is 24 to 72h.
[0012] Optionally, the method for preparing the slurry includes: Carbon-based materials and magnetic materials are added to a 0.5-5 wt% nanocellulose aqueous dispersion and stirred until homogeneous.
[0013] Secondly, the present invention provides a cellulose-based broadband lightweight multilayer microwave absorbing material, which is prepared by any of the preparation methods described above.
[0014] Compared with the prior art, the present invention has at least the following beneficial effects: Carbon-based materials have the advantages of low density and high dielectric loss, but lack magnetic loss, have poor impedance matching, and weak loss capability. Therefore, combining carbon-based materials with magnetic materials is an effective way to achieve synergistic performance.
[0015] Cellulose, as a natural polymer, has advantages such as wide availability, biodegradability, and ease of molding. Multilayer composites with varying dielectric constants can form gradient impedance matching, achieving broadband microwave absorption. Attached Figure Description
[0016] To more clearly illustrate the technical solutions in the embodiments of the present invention or the prior art, the drawings used in the description of the embodiments or the prior art will be briefly introduced below. Obviously, the drawings described below are some embodiments of the present invention. For those skilled in the art, other drawings can be obtained based on these drawings without creative effort.
[0017] Figure 1 This is a reflection loss data diagram of the cellulose-based broadband lightweight multilayer absorbing material provided in Embodiment 1 of the present invention in the frequency range of 2-18GHz; Figure 2 This is a reflection loss data diagram of the cellulose-based broadband lightweight multilayer absorbing material provided in Embodiment 2 of the present invention in the frequency range of 2-18GHz; Figure 3This is a reflection loss data diagram of the cellulose-based broadband lightweight multilayer absorbing material provided in Embodiment 3 of the present invention in the frequency range of 2-18 GHz; Figure 4 This is a graph showing the reflection loss data of the cellulose-based broadband lightweight multilayer absorbing material provided in Comparative Example 1 of the present invention in the frequency range of 2-18 GHz. Figure 5 This is a graph showing the reflection loss data of the cellulose-based broadband lightweight multilayer absorbing material provided in Comparative Example 3 of the present invention in the frequency range of 2-18 GHz. Detailed Implementation
[0018] To make the objectives, technical solutions, and advantages of the embodiments of the present invention clearer, the technical solutions of the embodiments of the present invention will be clearly and completely described below with reference to the accompanying drawings. Obviously, the described embodiments are some embodiments of the present invention, but not all embodiments. All other embodiments obtained by those skilled in the art based on the embodiments of the present invention without creative effort are within the scope of protection of the present invention.
[0019] This invention provides a method for preparing a cellulose-based broadband lightweight multilayer microwave absorbing material, comprising: Multiple groups of slurries are prepared, the slurries comprising carbon-based materials, magnetic materials, and a cellulose matrix; wherein, the amounts of carbon-based materials and magnetic materials added in different groups of slurries are different, so that the dielectric constants of the different groups of slurries are different after curing; Multiple sets of slurries are cured so that each set of slurries forms a composite layer after curing, resulting in a multilayer microwave absorbing material. In the multilayer composite layer of the multilayer microwave absorbing material, the dielectric constant gradient decreases from the bottom layer to the top layer; the top layer is the layer that receives electromagnetic waves.
[0020] In this embodiment, carbon-based materials have the advantages of low density and high dielectric loss, but lack magnetic loss, have poor impedance matching, and weak loss capability. Therefore, combining carbon-based materials with magnetic materials is an effective way to achieve synergistic performance. Specifically, by adjusting the ratio and amount of carbon-based / magnetic materials, the electromagnetic parameters can be flexibly controlled to meet the requirements of different frequency bands. At the same time, the multilayer dielectric gradient structure effectively optimizes the impedance matching of electromagnetic waves from air to the interior of the material, reduces surface reflection, enhances loss capability, and achieves broadband strong absorption.
[0021] Cellulose, as a natural polymer, has advantages such as wide availability, biodegradability, and ease of molding. Multilayer composites with varying dielectric constants can form gradient impedance matching, achieving broadband microwave absorption.
[0022] In some embodiments of the present invention, the carbon-based material is one of graphene, carbon nanotubes, and carbon black; the magnetic material is an iron-silicon-aluminum magnetic material modified with nanocellulose; and the cellulose matrix is nanocellulose.
[0023] In some embodiments of the present invention, the slurry further includes a crosslinking agent, which is a mixture of citric acid and phytic acid.
[0024] In this embodiment, the use of crosslinking agents is crucial to the structural stability of cellulose aerogels. Citric acid, as a polycarboxylic acid, can undergo esterification crosslinking with cellulose, while phytic acid contains multiple phosphate groups, which can not only crosslink cellulose but also coordinate with metal ions, improving interfacial polarization and enhancing electromagnetic wave loss capability. The two work synergistically to improve the structural stability and microwave absorption performance of the material.
[0025] In some embodiments of the present invention, the mass ratio of citric acid to phytic acid is 1:3 to 3:1, and the total amount of crosslinking agent added is 5% to 30% of the mass of nanocellulose.
[0026] In some embodiments of the present invention, the mass ratio of the carbon-based material to the magnetic material in the slurry is 1:10 to 10:1; the total filling amount of the carbon-based material and the magnetic material in the slurry accounts for 5% to 40% of the weight of the cellulose matrix layer.
[0027] In some embodiments of the present invention, the nanocellulose-modified iron-silicon-aluminum magnetic material is prepared by the following method: The mixture of nanocellulose solution and iron-silicon-aluminum powder at a mass ratio of 1:5 to 5:1 was ultrasonically dispersed and then freeze-dried to obtain the product; wherein the particle size of the iron-silicon-aluminum powder was 1 to 50 μm.
[0028] In some embodiments of the present invention, the curing method of the slurry includes sequential directional freeze drying and thermal crosslinking curing.
[0029] In this embodiment, aerogel structures can be prepared by directional freeze-drying to achieve lightweight properties. Furthermore, directional freeze-drying technology can construct anisotropic channels. Directional freeze-drying can form multilayer structures in one step, eliminating the need for subsequent impregnation or layer assembly, simplifying the process. Moreover, the directional arrangement of channels is beneficial for multiple reflections and attenuation of electromagnetic waves.
[0030] In some embodiments of the present invention, the process parameters for directional freeze drying are as follows: the directional freezing temperature is -80℃ to -20℃, the freezing rate is 0.5 to 5℃ / min, the vacuum degree of vacuum freeze drying is less than 20Pa, and the drying time is 24 to 72h.
[0031] In some embodiments of the present invention, the method for preparing the slurry includes: Carbon-based materials and magnetic materials are added to a 0.5-5 wt% nanocellulose aqueous dispersion and stirred until homogeneous.
[0032] This invention provides a cellulose-based broadband lightweight multilayer microwave absorbing material, which is prepared by any of the preparation methods described above.
[0033] To more clearly illustrate the technical solution and advantages of the present invention, the following describes the solution of this application in detail through several embodiments.
[0034] Example 1: (1) Preparation of nanocellulose-modified iron-silicon-aluminum: The aqueous dispersion of nanocellulose (NFC, solid content 1wt%) and iron-silicon-aluminum powder (average particle size 10μm) were mixed at a mass ratio of 2:1, ultrasonically dispersed for 30min, and then freeze-dried for 48h to obtain nanocellulose-modified iron-silicon-aluminum composite powder. (2) Multilayer slurry preparation: A three-layer structure was designed, with the concentration of nanocellulose matrix in each layer being 2 wt%; 1) Take graphene and modified iron-silicon-aluminum in a mass ratio of 8:2, with a total filling amount of 30% (relative to the dry weight of nanocellulose); take citric acid and phytic acid in a mass ratio of 1:1, with an addition amount of 15% (relative to nanocellulose); add graphene and modified iron-silicon-aluminum to NFC dispersion, stir for 1 hour, then add citric acid and phytic acid, stir for 30 minutes, and record as slurry 1#; 2) Take graphene and modified iron-silicon-aluminum in a mass ratio of 5:5, with a total filling amount of 20% (relative to the dry weight of nanocellulose); take citric acid and phytic acid in a mass ratio of 1:1, with an addition amount of 15% (relative to nanocellulose); add graphene and modified iron-silicon-aluminum to NFC dispersion, stir for 1 hour, then add citric acid and phytic acid, stir for 30 minutes, and record as slurry 2#; 3) Take graphene and modified iron-silicon-aluminum in a mass ratio of 2:8, with a total filling amount of 10% (relative to the dry weight of nanocellulose); take citric acid and phytic acid in a mass ratio of 1:1, with an addition amount of 15% (relative to nanocellulose); add graphene and modified iron-silicon-aluminum to NFC dispersion, stir for 1 hour, then add citric acid and phytic acid, stir for 30 minutes, and record as slurry 3#; (3) Directional freeze drying molding: The mold is a polytetrafluoroethylene square channel (150×150×30mm) 3 The bottom of the mold is in contact with the directional freezing table (-60℃). First, pour slurry #1 into the mold to a depth of 5mm, control the freezing rate at 2℃ / min, and after it is completely solidified, carefully pour slurry #2 on top of the solidified layer to a depth of 4mm. Under the same freezing conditions, finally pour slurry #3 onto the top layer to a depth of 3mm. After freezing, transfer the whole mold to a freeze dryer at -50℃ for 48 hours. (4) Thermal crosslinking and curing: The prepared sample was placed in an oven and heat-treated at 150°C for 3 hours. After natural cooling, a cellulose-based broadband lightweight multilayer microwave absorbing material was obtained.
[0035] The density of the sample was tested to be 32 kg / m³. 3 Four samples were spliced together to form a 300×300 mm sample. The reflectivity performance of the sample was tested, and the results are as follows. Figure 1 As shown, the minimum reflection loss of the absorbing material prepared in this embodiment is -47.2dB, and the effective absorption bandwidth is 10.6GHz (5.3~15.9GHz).
[0036] Example 2: (1) Preparation of nanocellulose-modified iron-silicon-aluminum: The aqueous dispersion of nanocellulose (NFC, solid content 1wt%) and iron-silicon-aluminum powder (average particle size 10μm) were mixed at a mass ratio of 2:1, ultrasonically dispersed for 30min, and then freeze-dried for 48h to obtain nanocellulose-modified iron-silicon-aluminum composite powder. (2) Multilayer slurry preparation: A three-layer structure was designed, with the concentration of nanocellulose matrix in each layer being 2 wt%; 1) Take carbon fiber and modified iron-silicon-aluminum in a mass ratio of 6:4, with a total filling amount of 25% (relative to the dry weight of nanocellulose); take citric acid and phytic acid in a mass ratio of 2:1, with an addition amount of 20% (relative to nanocellulose); add carbon fiber and modified iron-silicon-aluminum to NFC dispersion, stir for 1 hour, then add citric acid and phytic acid, stir for 30 minutes, and record as slurry 1#; 2) Take carbon fiber and modified iron-silicon-aluminum in a mass ratio of 4:6, with a total filling amount of 20% (relative to the dry weight of nanocellulose); take citric acid and phytic acid in a mass ratio of 2:1, with an addition amount of 20% (relative to nanocellulose); add carbon fiber and modified iron-silicon-aluminum to NFC dispersion, stir for 1 hour, then add citric acid and phytic acid, stir for 30 minutes, and record as slurry 2#; 3) Take carbon fiber and modified iron-silicon-aluminum in a mass ratio of 2:8, with a total filling amount of 15% (relative to the dry weight of nanocellulose); take citric acid and phytic acid in a mass ratio of 2:1, with an addition amount of 20% (relative to nanocellulose); add carbon fiber and modified iron-silicon-aluminum to NFC dispersion, stir for 1 hour, then add citric acid and phytic acid, stir for 30 minutes, and record as slurry 3#; (3) Directional freeze drying molding: The mold is a polytetrafluoroethylene square channel (150×150×30mm) 3The bottom of the mold is in contact with the directional freezing table (-80℃). First, pour the No. 1 slurry into the mold to a depth of 5mm, control the freezing rate to 1℃ / min, and after it is completely solidified, carefully pour the No. 2 slurry on top of the solidified layer to a depth of 4mm. Under the same freezing conditions, finally pour the No. 3 slurry onto the top layer to a depth of 3mm. After freezing, transfer the whole thing to a freeze dryer and dry at -50℃ for 48 hours. (4) Thermal crosslinking and curing: The prepared sample was placed in an oven and heat-treated at 180°C for 2 hours. After natural cooling, a cellulose-based broadband lightweight multilayer microwave absorbing material was obtained.
[0037] The sample density was tested to be 38 kg / m³. 3 Four samples were spliced together to form a 300×300 mm sample. The reflectivity performance of the sample was tested, and the results are as follows. Figure 2 As shown, the minimum reflection loss of the absorbing material prepared in this embodiment is -41.5dB, and the effective absorption bandwidth is 9.8GHz (8.2~18.0GHz).
[0038] Example 3: (1) Preparation of nanocellulose-modified iron-silicon-aluminum: The aqueous dispersion of nanocellulose (NFC, solid content 1wt%) and iron-silicon-aluminum powder (average particle size 10μm) were mixed at a mass ratio of 2:1, ultrasonically dispersed for 30min, and then freeze-dried for 48h to obtain nanocellulose-modified iron-silicon-aluminum composite powder. (2) Multilayer slurry configuration: A five-layer structure was designed, with the concentration of nanocellulose matrix at 2wt%; 1) Take graphene and modified iron-silicon-aluminum in a mass ratio of 9:1, with a total filling amount of 35% (relative to the dry weight of nanocellulose); take citric acid and phytic acid in a mass ratio of 1:2, with an addition amount of 10% (relative to nanocellulose); add graphene and modified iron-silicon-aluminum to NFC dispersion, stir for 1 hour, then add citric acid and phytic acid, stir for 30 minutes, and record as slurry 1#; 2) Take graphene and modified iron-silicon-aluminum in a mass ratio of 7:3, with a total filling amount of 30% (relative to the dry weight of nanocellulose); take citric acid and phytic acid in a mass ratio of 1:2, with an addition amount of 10% (relative to nanocellulose); add graphene and modified iron-silicon-aluminum to NFC dispersion, stir for 1 hour, then add citric acid and phytic acid, stir for 30 minutes, and record as slurry 2#; 3) Take graphene and modified iron-silicon-aluminum in a mass ratio of 5:5, with a total filling amount of 25% (relative to the dry weight of nanocellulose); take citric acid and phytic acid in a mass ratio of 1:2, with an addition amount of 10% (relative to nanocellulose); add graphene and modified iron-silicon-aluminum to NFC dispersion, stir for 1 hour, then add citric acid and phytic acid, stir for 30 minutes, and record as slurry 3#; 4) Take graphene and modified iron-silicon-aluminum in a mass ratio of 7:3, with a total filling amount of 20% (relative to the dry weight of nanocellulose); take citric acid and phytic acid in a mass ratio of 1:2, with an addition amount of 10% (relative to nanocellulose); add graphene and modified iron-silicon-aluminum to NFC dispersion, stir for 1 hour, then add citric acid and phytic acid, stir for 30 minutes, and record as slurry 4#; 5) Take graphene and modified iron-silicon-aluminum in a mass ratio of 1:9, with a total filling amount of 15% (relative to the dry weight of nanocellulose); take citric acid and phytic acid in a mass ratio of 1:2, with an addition amount of 10% (relative to nanocellulose); add graphene and modified iron-silicon-aluminum to NFC dispersion, stir for 1 hour, then add citric acid and phytic acid, stir for 30 minutes, and record as slurry 5#; (3) Directional freeze drying molding: The mold is a polytetrafluoroethylene square channel (150×150×30mm) 3 The bottom of the mold is in contact with the directional freezing table (-40℃). First, pour slurry #1 into the mold to a depth of 5mm, control the freezing rate at 3℃ / min, and after it is completely solidified, carefully pour slurry #2 on top of the solidified layer to a depth of 4mm. Under the same freezing conditions, after it is completely solidified, pour slurry #3 on top of the solidified layer to a depth of 3mm. After it is completely solidified, pour slurry #4 on top of the solidified layer to a depth of 2mm. After it is completely solidified, pour slurry #5 on top of the solidified layer to a depth of 1mm. After freezing, transfer the whole piece to a freeze dryer and dry at -50℃ for 48 hours. (4) Thermal crosslinking and curing: The prepared sample was placed in an oven and heat-treated at 120°C for 6 hours. After natural cooling, a cellulose-based broadband lightweight multilayer microwave absorbing material was obtained.
[0039] The sample density was measured to be 45 kg / m³. 3 Four samples were spliced together to form a 300×300 mm sample. The reflectivity performance of the sample was tested, and the results are as follows. Figure 3 As shown, the minimum reflection loss of the absorbing material prepared in this embodiment is -52.1dB, and the effective absorption bandwidth is 12.3GHz (3.65~15.95GHz).
[0040] Comparative Example 1: (1) Preparation of nanocellulose-modified iron-silicon-aluminum: The aqueous dispersion of nanocellulose (NFC, solid content 1wt%) and iron-silicon-aluminum powder (average particle size 10μm) were mixed at a mass ratio of 2:1, ultrasonically dispersed for 30min, and then freeze-dried for 48h to obtain nanocellulose-modified iron-silicon-aluminum composite powder. (2) Multilayer slurry preparation: single-layer structure, with a nanocellulose matrix concentration of 2wt%; Take graphene and modified iron-silicon-aluminum in a mass ratio of 5:5, with a total filling amount of 20% (relative to the dry weight of nanocellulose); take citric acid and phytic acid in a mass ratio of 1:1, with an addition amount of 15% (relative to nanocellulose); add graphene and modified iron-silicon-aluminum to NFC dispersion, stir for 1 hour, then add citric acid and phytic acid, and stir for 30 minutes. (3) Directional freeze drying molding: The mold is a polytetrafluoroethylene square channel (150×150×30mm) 3 The bottom of the mold is in contact with the directional freezing table (-60℃); the slurry is poured into the mold to a depth of 12mm, and the freezing rate is controlled at 2℃ / min. After freezing, the whole thing is transferred to a freeze dryer and dried at -50℃ for 48 hours. (4) Thermal crosslinking and curing: The prepared sample was placed in an oven and heat-treated at 150°C for 3 hours. After natural cooling, a cellulose-based broadband lightweight multilayer microwave absorbing material was obtained.
[0041] Four samples were spliced together to form a 300×300 mm sample. The reflectivity performance of the sample was tested, and the results are as follows. Figure 4 As shown, the minimum reflection loss of the absorbing material prepared in this comparative example is -38.6dB, and the effective absorption bandwidth is 7.1GHz (4.95~12.05GHz).
[0042] Comparative Example 2: Same as Example 1, but without the addition of citric acid and phytic acid, the resulting material is brittle, shrinks severely after drying (volume shrinkage rate 45%), collapses in structure, cannot form a complete multi-layer gradient, and cannot be tested for microwave absorption performance.
[0043] Comparative Example 3: Same as Example 1, but only citric acid (15%) was added, phytic acid was not added. Four samples were spliced together to form a 300×300 sample, and the reflectivity performance of the sample was tested. The results are as follows. Figure 5 As shown, the microwave absorbing material prepared in this embodiment has a complete structure after cross-linking, but its microwave absorption performance is weakened in the 2~18GHz range. This proves that the introduction of phytic acid can enhance the synergistic effect of interfacial polarization and magnetic loss. Its minimum reflection loss is -32.4dB and its effective absorption bandwidth is 9.3GHz (5.45~14.75GHz).
[0044] Finally, it should be noted that the above embodiments and comparative examples are only used to illustrate the technical solutions of the present invention, and not to limit them. Although the present invention has been described in detail with reference to the foregoing embodiments and comparative examples, those skilled in the art should understand that modifications can still be made to the technical solutions described in the foregoing embodiments and comparative examples, or equivalent substitutions can be made to some of the technical features. Such modifications or substitutions do not cause the essence of the corresponding technical solutions to deviate from the spirit and scope of the technical solutions of the embodiments and comparative examples of the present invention.
Claims
1. A method for preparing a cellulose-based broadband lightweight multilayer microwave absorbing material, characterized in that, include: Multiple groups of slurries are prepared, the slurries comprising carbon-based materials, magnetic materials, and a cellulose matrix; wherein, the amounts of carbon-based materials and magnetic materials added in different groups of slurries are different, so that the dielectric constants of the different groups of slurries are different after curing; Multiple sets of slurries are cured so that each set of slurries forms a composite layer after curing, resulting in a multilayer microwave absorbing material. In the multilayer composite layer of the multilayer microwave absorbing material, the dielectric constant gradient decreases from the bottom layer to the top layer; the top layer is the layer that receives electromagnetic waves.
2. The preparation method according to claim 1, characterized in that, The carbon-based material is one of graphene, carbon nanotubes, and carbon black; the magnetic material is an iron-silicon-aluminum magnetic material modified with nanocellulose; and the cellulose matrix is nanocellulose.
3. The preparation method according to claim 1, characterized in that, The slurry also includes a crosslinking agent, which is a mixture of citric acid and phytic acid.
4. The preparation method according to claim 3, characterized in that, The mass ratio of citric acid to phytic acid is 1:3 to 3:1, and the total amount of crosslinking agent added is 5% to 30% of the mass of nanocellulose.
5. The preparation method according to claim 1, characterized in that, The mass ratio of the carbon-based material to the magnetic material in the slurry is 1:10 to 10:1; the total filling amount of the carbon-based material and the magnetic material in the slurry accounts for 5% to 40% of the weight of the cellulose matrix layer.
6. The preparation method according to claim 2, characterized in that, The nanocellulose-modified iron-silicon-aluminum magnetic material was prepared by the following method: The mixture of nanocellulose solution and iron-silicon-aluminum powder at a mass ratio of 1:5 to 5:1 was ultrasonically dispersed and then freeze-dried to obtain the product; wherein the particle size of the iron-silicon-aluminum powder was 1 to 50 μm.
7. The preparation method according to claim 1, characterized in that, The curing method of the slurry includes sequential directional freeze drying and thermal crosslinking curing.
8. The preparation method according to claim 7, characterized in that, The process parameters for directional freeze drying are as follows: the directional freezing temperature is -80℃ to -20℃, the freezing rate is 0.5 to 5℃ / min, the vacuum degree of vacuum freeze drying is less than 20Pa, and the drying time is 24 to 72h.
9. The preparation method according to claim 1, characterized in that, The method for preparing the slurry includes: Carbon-based materials and magnetic materials are added to a 0.5-5 wt% nanocellulose aqueous dispersion and stirred until homogeneous.
10. A cellulose-based broadband lightweight multilayer microwave absorbing material, characterized in that, It is prepared by any of the preparation methods described in claims 1-9.